2022
DOI: 10.1073/pnas.2119187119
|View full text |Cite
|
Sign up to set email alerts
|

ERK signaling dissolves ERF repression condensates in living embryos

Abstract: Phase separation underlies the organization of the nucleus, including the biogenesis of nucleoli and the packaging of heterochromatin. Here we explore the regulation of transcription factor condensates involved in gene repression by ERK signaling in gastrulating embryos of a simple proto-vertebrate (Ciona). ERK signaling induces nuclear export of the transcriptional repressor Ets-2 repressive factor (ERF), which has been linked to various human developmental disorders. Using high-resolution imaging, we show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…the relation between the fraction of phosphorylated activator, A p and active ERK, Erk � . Lower panel: Heatmaps showing the Hill coefficients of the relation between Otx and Erk � when changing the values of the k MMi in Eqs (16)(17). (E) Relation between the level of Otx expression predicted by the model (O) and cell surface in contact with FGF-expressing mesendoderm cells (S 1 ) in the presence (blue curve, Hill coefficient = 14.2) or in the absence (orange curve, Hill coefficient = 5.7) of the repressor I.…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…the relation between the fraction of phosphorylated activator, A p and active ERK, Erk � . Lower panel: Heatmaps showing the Hill coefficients of the relation between Otx and Erk � when changing the values of the k MMi in Eqs (16)(17). (E) Relation between the level of Otx expression predicted by the model (O) and cell surface in contact with FGF-expressing mesendoderm cells (S 1 ) in the presence (blue curve, Hill coefficient = 14.2) or in the absence (orange curve, Hill coefficient = 5.7) of the repressor I.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…To obtain an expression for Otx expression (O and Otx smFISH ) as a function of the inputs of the signaling cascade (S 1 ) we combined the models of ERK activity and of Otx expression presented in the previous sections. We computed ERK activity using Eq (1) and we used this as the input (Erk � ) to compute the fraction of active Ets1/2 (A p ) and active ERF2 (I) using Eqs ( 16) and (17). Then we computed the level of Otx expression by solving Eq (15).…”
Section: Model Of Otx Expressionmentioning
confidence: 99%
“…In contrast, the transcription of the immediate-early gene Otx is bimodal, with a ON response that is restricted to neural precursors. We hypothesized that the ON/OFF response is, at least in part, due to the dual control of Otx expression (Williaume et al, 2021): ETS1/2 phosphorylation by ERK is required for its transcriptional activator activity (Weaver et al, 2022), while phosphorylation of the ERF2 repressor by dpERK promotes its nuclear export, thus preventing its binding to DNA (Le Gallic et al, 1999;2004) (Fig. 1A).…”
Section: Dual Control Of the Expression Of The Otx Gene By Erkmentioning
confidence: 99%
“…The Ets2 repressor factor 2 (ERF2) (Yagi et al, 2003) recognizes the same binding site as the transcriptional activator ETS1/2 and its activity is negatively controlled by ERK via nuclear export (Le Gallic et al, 1999;2004;and Weaver et al, 2022). Thus, we considered that Otx expression is enhanced by the stimulation of an activator (A; e.g.…”
Section: Model Of Otx Expressionmentioning
confidence: 99%
“…ERF was also shown to repress Otx in Ciona embryos at the 32-cell stage (Williaume et al 2021). Interestingly, we previously observed that ERF condensates were able to dissolve and reform within a single interphase (Weaver et al 2022), suggesting a dynamic response to endogenous FGF signals.…”
Section: Introductionmentioning
confidence: 99%